Realizing Visible Light Excitation of Tb3+ via Highly Efficient Energy Transfer from Ce3+ for LED‐Based Applications. Issue 9 (20th February 2019) - Xiao, Wenge; Liu, Xiaofeng; Zhang, Jiahua; Qiu, Jianrong
Abstract: Trivalent terbium (Tb 3+ )‐activated luminescence materials usually show highly efficient green emission with the full width at half maximum of merely 10 nm, but suffer from the unsatisfactory excitable wavelength (<380 nm) as well as the inefficient light absorption. Here, the realization of efficient visible light excitation of Tb 3+ is demonstrated in terbium‐concentrated garnet Ca2 TbHf2 Al3 O12 (CTHA) by introducing Ce 3+ as the sensitizer. Owing to highly efficient energy transfer from Ce 3+ to Tb 3+, CTHA:Ce 3+ combines advantages of the extra narrow green emission of Tb 3+ peaking at 544 nm and the efficient broad excitation of Ce 3+ covering the short‐wavelength visible light from 380 to 450 nm. The color gamut of the prototype white light‐emitting diode (LED) by using CTHA:Ce 3+ as the green emitter can reach 95% (coverage ratio) of National Television Standards Committee (NTSC) space in Commission Internationale de L'Eclairage (CIE) 1931, indicating its great potential for LED (or laser diode)‐based applications. Abstract : Efficient visible light excitation of Tb 3+ is realized in Ca2 TbHf2 Al3 O12 :Ce 3+ owing to highly efficient energy transfer from Ce 3+ to Tb 3+, which shows intense green emission with extra narrow band of merely 10 nm upon the excitation of the short‐wavelength visible light from 380 to 450 nm, indicating its great potential for light‐emitting diode or laser diode applications.